2008
DOI: 10.1080/17470210701822967
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Mental Rotation with Polygons of Different Complexity: Do Men Utilize Holistic Processes whereas Women Prefer Piecemeal Ones?

Abstract: Sex differences in mental rotation were investigated as a function of stimulus complexity with a sample size of N = 72. Replicating earlier findings with polygons, mental rotation was faster for males than for females, and reaction time increased with more complex polygons. Additionally, sex differences increased for complex polygons. Most importantly, however, mental rotation speed decreased with increasing complexity for women but did not change for men. Thus, the sex effects reflect a difference in strategy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
131
2
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(153 citation statements)
references
References 19 publications
10
131
2
6
Order By: Relevance
“…The current study found that the exponent values were larger overall for females than for males, suggesting that females were less reliant on a mental rotation strategy to decide if rotated objects would face to the left or to the right when imagined at the upright. This finding is consistent with research suggesting that strategy differences exist on mental rotation tasks when comparing the performances of males and females (Butler et al, 2006;Heil & Jansen-Osmann, 2008;Hirnstein, Bayer, & Hausmann, 2009). While these sex difference findings are interesting, they are presented with caution as the group sizes were small when comparing the parameters of males and females.…”
Section: Discussionsupporting
confidence: 89%
“…The current study found that the exponent values were larger overall for females than for males, suggesting that females were less reliant on a mental rotation strategy to decide if rotated objects would face to the left or to the right when imagined at the upright. This finding is consistent with research suggesting that strategy differences exist on mental rotation tasks when comparing the performances of males and females (Butler et al, 2006;Heil & Jansen-Osmann, 2008;Hirnstein, Bayer, & Hausmann, 2009). While these sex difference findings are interesting, they are presented with caution as the group sizes were small when comparing the parameters of males and females.…”
Section: Discussionsupporting
confidence: 89%
“…It is important to note that our findings replicated the classic angular disparity effect (ADE; e.g., Blough & Slavin, 1987;Collins & Kimura, 1997;Cooper, 1975;Heil & Jansen-Osmann, 2008;Kail et al, 1979;Maccoby & Jacklin, 1974;Shepard & Metzler, 1971). ADE shows that rotation performance is directly affected by the angular difference between objects.…”
Section: Discussionsupporting
confidence: 76%
“…It has been a long debate how humans deal with complexity (Heil & Jansen-Osmann, 2008). Across different disciplines it is generally assumed (and experimentally confirmed) that humans will reduce complexity and lower the individual pieces of information that they have to deal with (Cowan, 2001).…”
Section: Discussionmentioning
confidence: 99%